Intensification of Surfactant Synthesis in Rhodococcus erythropolis EK-1 Cultivated on Hexadecane - Pirog, Tatiana; Klimenko, Julia; Shevchuk, Tetiana (My University, 2010)
Activity of key enzymes of n-alkane metabolism was determined in cells of Rhodococcus erythropolis EK-1, a surfactant producer grown on n hexadecane. Potassium cations were found to inhibit alkane hydroxylase and NADP+-dependent aldehyde dehydrogenase, while sodium cations were found to activate these enzymes. Decreased potassium concentration (to 1 mM), increased sodium concentration (to 35 mM), and addition of 36 μmol/l Fe(II), required for alkane hydroxylase activity, resulted in increased activity of the enzymes of n-hexadecane metabolism and in a fourfold increase of surfactant synthesis. A 1.5–1.7-fold increase in surfactant concentration after addition of 0.2% fumarate (gluconeogenesis precursor) and 0.1% citrate (lipid synthesis regulator) to the medium with hexadecane results from enhanced synthesis of trehalose mycolates, as evidenced by a 3–5- fold increase in phosphoenolpyruvate synthetase and trehalose phosphate synthase, respectively.В клетках штамма-продуцента поверхностно-активных веществ (ПАВ) Rhodococcus erythropolis ЭК-1, выращенного на н-гексадекане, определена активность ключевых ферментов метаболизма н-алканов.
Keywords: intensification; Rhodococcus erythropolis ЕК-1; n-alkane metabolism; surfactant; інтенсифікація; метаболізм н-алканів; поверхнево-активні речовини; кафедра біотехнології і мікробіології